Estimation of Rhizophora mucronata carbon stock in Youtefa bay, Jayapura, Papua - Indrayani, Ervina; Kalor, John D; Hisyam, Muhammad; Waum, Ida (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Papua island has the largest mangrove forest area in Indonesia, reaching 1,350,600.00 Ha which accounts for half of the entire area of mangrove forests in Indonesia. One of the locations with a fairly extensive mangrove forest in the Jayapura area is in Youtefa Bay. Although mangroves have large environmental potential, local people use the forest as building materials, food, fishing tools, and medicines. Mangrove forests have an active role in maintaining global climate stability in the world, forest vegetation will fix CO2 through the process of photosynthesis. Mangrove forests per hectare can store up to four times more carbon than other tropical forests worldwide. This research aims to estimate the amount of carbon stock Rhizophora mucronata can store in mangrove forests in Youtefa Bay, particulary in Tobati, Enggros and Entrop Villages, Jayapura, Papua. The method used in this study was using Allometric Equations to estimate the biomass carbon from Rhizophora mucronata and compared to three different satellite imagery algorithms. The research results showed that the biomass of Rhizophora mucronata stands in Entrop Village was the highest and the lowest in Enggros Village. In addition, the results of measurements of carbon stocks in Tobati and Enggros Villages showed that the values were similar, only 0.23 kgC/m2 with carbon stocks in Entrop Village reaching 19.46 kgC/m2. Based on the results of measuring satellite imagery with three different algorithms, it was found that using the EVI algorithm produced the smallest Standard Error of Estimate, which was 1.63 kg C/m2. The estimated total carbon in Youtefa Bay is 213,424.69 kg C/m2.Keywords:AllometricCarbon StockRhizophora mucronataYoutefa Bay